Value of severity scales in predicting mortality from community-acquired pneumonia: systematic review and meta-analysis. Issue 10 (20th August 2010) - Loke, Yoon K; Kwok, Chun Shing; Niruban, Alagaratnam; Myint, Phyo K
Abstract : Background: Several scoring systems have been used to predict mortality in patients with community-acquired pneumonia. The properties of commonly used risk stratification scales were systematically reviewed. Methods: MEDLINE and EMBASE (January 1999–October 2009) were searched for prospective studies that reported mortality at 4–8 weeks in patients with radiographically-confirmed community-acquired pneumonia. The search focused on the Pneumonia Severity Index (PSI) and the three main iterations of the CURB (confusion, urea nitrogen, respiratory rate, blood pressure) scale (CURB-65, CURB, CRB-65), and test performance was evaluated based on 'higher risk' categories as follows: PSI class IV/V, CURB-65 (score ≥3), CURB (score ≥2) and CRB-65 (score ≥2). Random effects meta-analysis was used to generate summary statistics of test performance and receiver operating characteristic curves were used for predicting mortality. Results: 402 articles were screened and 23 studies involving 22 753 participants (average mortality 7.4%) were retrieved. The respective diagnostic odds ratios for mortality were 10.77 (PSI), 6.40 (CURB-65), 5.97 (CRB-65) and 5.75 (CURB). Overall, PSI had the highest sensitivity and lowest specificity for mortality, CRB-65 was the most specific (but least sensitive) test and CURB-65/CURB were between the two. Negative predictive values for mortality were similar among the tests, ranging from 0.94 (CRB-65) to 0.98 (PSI), whereas positive predictive values ranged from 0.14 (PSI) to 0.28 (CRB-65). Conclusions: The current risk stratification scales (PSI, CURB-65, CRB-65 and CURB) have different strengths and weaknesses. All four scales had good negative predictive values for mortality in populations with a low prevalence of death but were less useful with regard to positive predictive values.